Modals and conditionals - Kratzer, Angelika (Oxford : Oxford University Press, 2012)
This text contains updated and substantially revised versions of Angelika Kratzer's classic papers on modals and conditionals. It represents some of the most important work on modals and conditionals and the semantics-syntax interface and will be of interest to linguists and philosophers of language of all theoretical persuasions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Modality (Linguistics); Grammar, Comparative and general -- Conditionals